2002
DOI: 10.1101/gad.973602
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates cell survival by inhibiting PIK3CA in squamous cell carcinomas

Abstract: Interactions between the p53 and PI3K/AKT pathways play a significant role in the determination of cell death/survival. In benign cells these pathways are interrelated through the transcriptional regulation of PTEN by p53, which is required for p53-mediated apoptosis. PTEN exerts its effects by decreasing the phosphorylated AKT fraction, thereby diminishing prosurvival activities. However, the link between these pathways in cancer is not known. In this study, PIK3CA, encoding the p110␣ catalytic subunit of PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(170 citation statements)
references
References 26 publications
7
158
1
4
Order By: Relevance
“…However, there are conflicting data about the correlation of PIK3CA mutation and p53 mutations in cancer. Singh et al (2002) reported that PIK3CA and p53 mutations were mutually exclusive, while Maruyama et al (2007) could not find that associations. In our study, a trend was seen towards mutual exclusivity between PIK3CA mutations and p53 mutations (P ¼ 0.0687).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are conflicting data about the correlation of PIK3CA mutation and p53 mutations in cancer. Singh et al (2002) reported that PIK3CA and p53 mutations were mutually exclusive, while Maruyama et al (2007) could not find that associations. In our study, a trend was seen towards mutual exclusivity between PIK3CA mutations and p53 mutations (P ¼ 0.0687).…”
Section: Discussionmentioning
confidence: 97%
“…Then we were interested in studying the relationship between PI3K/AKT pathway and p53 (tumor suppressor gene) since interactions between the p53 and PI3K/ AKT pathways play a significant role in the determination of cell death/survival. Interrelation between these pathways occurs through the transcriptional regulation of PTEN by p53, which is required for p53-mediated apoptosis (Singh et al, 2002;Maruyama et al, 2007). However, there are conflicting data about the correlation of PIK3CA mutation and p53 mutations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, recent study showed that induction of P53 resulted in decreased in phosphorylated AKT activity in cell line, which did not express PTEN protein, thus highlighting that p53 was involved in regulation of survival PI3K/AKT pathway in epithelial tumors, and independently of PTEN expression. 12 It was reported that activation of p53-dependent downstream targets BAX with concomitant increase of MAPKinase (MAPK) pathways leading to apoptosis. 13 Altogether, these data indicated that the relationship between P53, PI3K/AKT and MAPK signaling pathways offers novel valuable insights into the resistance to targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of the different inhibitory mechanisms to Akt inactivation may vary among different cell types, as well as between normal and malignant cells. 111 Once again, this brings in the picture of p53 as a master regulator, which pulls simultaneously many strings when apoptosis has to be orchestrated ( Figure 5). …”
Section: P53 Mdm2 and Akt: A Matter Of Balance?mentioning
confidence: 99%
“…The finding that PTEN is a transcriptional target of p53 establishes an additional link in the network: activation of p53 will augment PTEN expression, which will incapacitate Akt and in this manner will further facilitate apoptosis. To make things even more interesting, p53 also represses the expression of the catalytic subunit of PI3 K. 111 Since PI3 K is a critical upstream activator of Akt, this inhibitory effect of p53 will also lead to Akt inactivation, which may cooperate with the induction of PTEN and the degradation of Akt to achieve effective p53-mediated attenuation of Akt function. The relative contribution of the different inhibitory mechanisms to Akt inactivation may vary among different cell types, as well as between normal and malignant cells.…”
Section: P53 Mdm2 and Akt: A Matter Of Balance?mentioning
confidence: 99%